Research of railway gauge modification systems - Balabekova К.Г.; Zabieva А.Б.; Orazalina А.Б. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The article examines the modification systems of railway gauges. Currently, when moving from one country to another, standard rails are transformed into railway relays from 1435 mm to 1520 mm. As a result of calculating the contact pressure between wheels and railways, the maximum contact pressure was at the level of 534 MPa, and this can be compared with the data in the reference book "contact pressure and service life", where the curve of the dependence of contact pressure on cycles shows 104 million cycles at the contact pressure level below the average score of 1. Based on the data in the handbook, although fatigue disorders due to wear are not expected at a contact pressure level of 534 MPa, fatigue disorders in the contact zone depend on the condition of the surface and external conditions, therefore it was decided that lubrication and maintenance of the surface should be carried out regularly.